2020
DOI: 10.1007/s13204-020-01347-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcium–silicate–hydrate (C–S–H) seeds on reference microorganisms

Abstract: Building materials are constantly improved with various additives and admixtures in order to achieve goals ranging from obtaining increased durability or antimicrobial activity up to reducing the carbon footprint left by the cement production. Since nanomaterials were proposed for cement products, many studies explored the possibilities for their incorporation. One of the novel trends in studying these materials is evaluating their impact on living organisms, with the focus not only on toxicology but also on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…After 6 and 12 h, other reads have strengthened the results, providing more insight into population growth and inhibition dynamics. The nanomaterials did not lead to complete inhibition of bacterial growth, similar to the observation made in the previous studies (Sikora et al 2018;Augustyniak et al 2020b). All nanomaterials containing titanium dioxide or carbon nanotubes caused a decrease in the OD, especially in the highest concentrations.…”
Section: Optical Density and Fluorescencesupporting
confidence: 88%
“…After 6 and 12 h, other reads have strengthened the results, providing more insight into population growth and inhibition dynamics. The nanomaterials did not lead to complete inhibition of bacterial growth, similar to the observation made in the previous studies (Sikora et al 2018;Augustyniak et al 2020b). All nanomaterials containing titanium dioxide or carbon nanotubes caused a decrease in the OD, especially in the highest concentrations.…”
Section: Optical Density and Fluorescencesupporting
confidence: 88%
“…In recent years, there is a growing concern about the safety of using NPs in cementitious composites. Thus, the amount of the research works increased substantially (Bräu et al 2012;Spinazzè et al 2016;Bossa et al 2017Bossa et al , 2019Diamond et al 2017;Miller et al 2017;Strokova et al 2018;Funk et al 2019;Torres-Carrasco et al 2019;Augustyniak et al 2020b). In Funk et al (2019) analyzed micro-and nano-components' release from cementitious composites containing TiO 2 and SiO 2 NPs after freeze-thawing.…”
Section: Introductionmentioning
confidence: 99%
“…In works (Bossa et al 2017(Bossa et al , 2019Diamond et al 2017), extensive evaluations on the release behavior and understanding the phenomena underlying the mechanism on releasing TiO 2 nanoparticles were performed. In our recent research (Augustyniak et al 2020b), the effects of commercially available and laboratory synthesized calcium-silicate-hydrate (C-S-H) nanostructures on the reference microorganisms were tested. These studies have shown that there, in some cases, the addition of C-S-H changes the growth environment for bacteria in a way that promotes their growth (Augustyniak et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations